China's rural development and the research of the agroecosystem in the recent years - Li, Zheng-Fang (Agroecosystem Research in Rural Resource Management and Development, 1985)
Progress in the study of China's agroecosystems in relation to recent changes in rural development policies are discussed. Key policy changes are: the new economy is combined with the household economy basis in the rural areas, agricultural production structure has been changed to ecological and synthetical agriculture, rural economy has undergone the transformation from original self-supporting or semi-self-supporting economy to the commodity economy which gives rise to the prosperity of the rural areas, economic activity of the commodity production is emerging in the untilled land around the household and the peasants begin to learn scientific knowledge and apply it to production